2005
DOI: 10.1111/j.1600-6143.2004.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Heart Allograft Survival by Immature Dendritic Cells Generated from Recipient Type Bone Marrow Progenitors

Abstract: Recent studies suggest that particular dendritic cells (DC) subpopulations may be tolerogenic. To test the capacity of different DC subpopulations to modulate allograft rejection, we generated two distinct populations of rat bone marrow-derived DCs (BMDC) with low doses of GM-CSF and IL-4. The non-adherent population (nBMDC), which are the 'classical' DCs was able to stimulate naïve allogeneic T cells and could be induced to completely mature using various stimuli. In contrast, the adherent population (aBMDC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 59 publications
8
127
0
1
Order By: Relevance
“…However, in the absence of infection, LN iDCs are important for induction and maintenance of T cell tolerance to peripheral Ags (36,58,59). Supporting this view, selective depletion of iDCs (and a reciprocal increase in the number of mature DCs) is a hallmark of a classical human autoimmune disease: systemic lupus erythematosus (60, 61).…”
Section: Discussionmentioning
confidence: 90%
“…However, in the absence of infection, LN iDCs are important for induction and maintenance of T cell tolerance to peripheral Ags (36,58,59). Supporting this view, selective depletion of iDCs (and a reciprocal increase in the number of mature DCs) is a hallmark of a classical human autoimmune disease: systemic lupus erythematosus (60, 61).…”
Section: Discussionmentioning
confidence: 90%
“…Recent studies have used immature donor DCs with the addition of costimulation blockade, revealing a synergistic effect in promoting long-term allograft survival (65). Interestingly, recipient-derived immature DCs also prolong allograft survival by a mechanism that is not donor specific and depends in part on the production of NO (66).…”
Section: Cells Of the Innate Immune System As Participants In Allogramentioning
confidence: 99%
“…It has been shown that graft rejection can be modulated by using non-modified, donor iDCs alone prior to transplantation (Fu, Li et al 1996;Lu, Li et al 1997). In addition, DC differentiation in the presence of GM-CSF and IL-4 at lower concentrations, results in generation of "semi-differentiated" adherent DCs with lower stimulatory capacity than their fully differentiated counterparts (Peche, Trinite et al 2005). In this manner, such adherent DCs administered just one day prior to transplantation induced significant prolongation of heart allograft survival and suppressed anti-donor humoral and cellular immune responses (Peche, Trinite et al 2005).…”
Section: Tdcs In Transplantationmentioning
confidence: 96%